Peran Guru Pendidikan Agama Kristen dan Orangtua dalam Mencegah Dampak Negatif Perkembangan Teknologi bagi Nara Didik - anugrah bt (Institut Agama Kristen Negeri Manado, 2023)
This research discusses the role of Christian religious education teachers and parents in preventing the negative impact of technological developments on children. The impact of technological developments is very significant both internally and externally. This is a reality that every human being needs to face. Therefore there needs to be a strategy in dealing with these technological developments. The purpose of this study is to explain the role of Christian religious teachers and parents in preventing the negative impacts of technological developments on children. The method used is descriptive qualitative method which focuses on collecting data through books, articles and relevant sources. As a result of this study, it was found that the role of Christian religious teachers and parents in preventing the negative impacts of technological developments on children is Christian religious education teachers providing education about technological developments for children at school, together with parents providing supervision of children's activities and relationships, providing activities positive for children both at school and outside of school, giving confidence to children through giving assignments